Analysis of Government Construction Tender Process Failures (Case Study: X Regency) - Shalahuddin Akmal; Rani Gayatri Kusumawardhani P (Eduvest - Journal of Universal Studies, 2025)
Indonesia, as a developing archipelagic country, emphasizes infrastructure development to boost the economy and enhance inter-island connectivity. Significant state budget allocations for construction annually underscore the sector's importance. However, in X Regency, many construction tenders have failed, leading to unabsorbed budgets and wasted resources. This study aims to identify factors causing tender failures and develop strategies to minimize them. Utilizing quantitative methods, the research includes questionnaire surveys and secondary data analysis from literature studies. The Relative Importance Index (RII) is employed to identify tender failure factors, and Multiple Criteria Decision Analysis (MCDA) is used to develop strategy implementations. The findings reveal ten critical factors contributing to tender failures: insufficient time for bidding document preparation, incomplete documents, failure to upload documents, unawareness of schedules, bidders' technical specifications not meeting requirements, Service User setting HPS too low, personnel qualifications not matching selection criteria, non-compliance with legal requirements, insufficient information causing multiple interpretations, and delayed learning of bid announcements.  Consequently, 46 strategic implementations are recommended. The top five strategies include: optimizing personnel rotation with appropriate qualifications for different projects, adding an article in the Regent Regulation regarding an Electronic Procurement Service hotline for system errors, recommending Service Providers re-examine auction activity requirements before registering, including an article in the Regent Regulation for evaluating tender processes to identify and address participant constraints,  and advising Service Users to conduct thorough market price surveys. These strategies aim to enhance tender processes, ensuring better absorption of allocated budgets and effective project execution.